The tectonic evolution of the Cape Fold Belt: constraints from fluid inclusion characteristics in syntectonic quartz veins - Proctor, Briony (Rhodes University, Faculty of Science, Department of Geology, 2017)
Syn-tectonic quartz veins formed along faults, folds and tension gashes in rocks of the Cape Supergroup (CSG) of the central Cape Fold Belt (CFB) comprise mainly hydrous saline fluids. These veins may also contain CO₂ Syn-tectonic quartz veins formed along faults, folds and tension gashes in rocks of the Cape Supergroup CO₂ , or CH4 and CO₂, or neither CO₂ nor CH4. The majority of inclusions are two-phase and fluid rich, and the most common fluid composition is H2O-NaCl. The final melting temperature, and therefore salinity, differs very little across different structures (fluids in all structures show maximum salinities between 2.5 and 6 wt% NaCl equivalent). Thrusts, reverse faults, strike- and oblique-slip faults, and folds all have similar homogenization temperatures (Th). Primary H2O-NaCl inclusions show Th between ~130 and 200 °C, and H2O-NaCl-CO₂ inclusions have slightly higher Th, between ~140 and 240 °C. Secondary inclusions in all structures have a similar Th range to primary inclusions, but have a lower maximum Th (~130-180 °C). Inclusions containing CH4 have the highest Th (~210 - 300 °C). Microthermobarometry indicates that fluids associated with contractional structures, such as thrust faults or folds, from the Ordovician lower Table Mountain Group (TMG) show lower greenschist facies trapping conditions (~170-175 MPa and ~240-300 °C). These veins also show a plastic deformation overprint (recrystallization of quartz and foam textures), at temperatures higher than the trapping conditions (~ ≥300 °C), indicating that temperatures increased subsequent to hydraulic fracturing, quartz precipitation and thrust slip. These structures formed on a prograde path, at approximately 335 Ma, at a time when the overlying CSG rock column was approximately 6800 m thick. This event pre-dated the thermal peak of the Cape Orogeny at ~276-261 Ma by ~60 million years. Further up in the stratigraphy of the CFB, in the Devonian upper Bokkeveld Group, fluid inclusions in quartz veins associated with a thrust fault show similar trapping pressure (~200 MPa) to the structures in the lower CFB. At 335 Ma, the stratigraphic overburden on this sample locality would not have been sufficiently thick to exert the calculated pressure. This fault may have formed at a later time. The observed pressure of ~200 MPa may have been created either by the higher Bokkeveld Group, the entire Witteberg Group, and further CSG rocks that were eroded prior to the deposition of the Permo-Triassic Karoo Supergroup, or by tectonic thickening of the CSG by prograde thrusting. Still further up in the CSG, fluids from a fold sample from the Witteberg Group record quartz precipitation at lower greenschist facies conditions and subsequent plastic deformation during folding. The formation of this fold postdates the thrusting in the lower TMG, and may correlate in time with deformation during the thermal peak in Middle Permian time (~276-261 Ma).
Keywords: Uncatalogued